Effect of mineral block supplementation on the productive performance of forage-fed guinea pigs - Castillo G., Carlos (2012)
The purpose of this study was to evaluate the effect of mineral block supplementation on the productive performance of guinea pigs in a forage-based rearing system under the Peruvian Central Coastal conditions. Thirty two 15-day weaned, male, Peru breed guinea pigs were randomly assigned to eight rearing boxes. A completely random design with two treatments and four replications was used in the study. Treatments were T0 (feeding with maize forage) and T1 (as T0 plus free access to blocks containing macro and microminerals). Body weight gain, feed intake, feed conversion and the economic merit were evaluated. There was statistical difference between treatments on body weight gain (T0: 358.8 and T1: 476.7 g) and feed conversion index (T0: 6.9 and T1: 5.5) (p<0.05), but without statistical difference on feed intake. It was 9% cheaper to produce 100 g body weight of guinea pig using mineral blocks. It is concluded that the use of mineral blocks has a potential to increase guinea pig productivity in the forage-based rearing system of the Peruvian Central Coast.